GROP: A genomic information repository for oilplants - Guo, Wenlei; Jin, Hongmiao; Chen, Junhao; Huang, Jianqin; Zheng, Dingwei; Cheng, Zhitao; Liu, Xinyao; Yang, Zhengfu; Chen, Fei; Lim, Kean-Jin; Wang, Zhengjia (Frontiers in Plant Science, 2022)
Biomass energy is an essential part of the agriculture economy and an important renewable energy source, particularly significant in fighting the energy crisis and global warming. Among them, oil plant resources are an indispensable part of biomass energy. The genomic data of oil plants mountains with the advancement of next-generation sequencing technology (NGS) in recent years. Based on these genomic data, we perform a combination of bioinformatic protocol to acquire the inner information of massive genomic data. Then a genomic information repository for oil plant genomic data was built through Django, Bootstrap, echarts etc website technology. We built the genomics repository of oil plants (http://grop.site/) as the portal for genomics research on oil plants. The current version of GROP integrates the coding sequences, protein sequences, genome structure, functional annotation information, and other information from 18 species, 22 genome assembly, and 46 transcriptomes. Additionally, GROP provides BLAST, genome browser, functional enrichment tool, and search tools. The massive genomic data of oil plants and bioinformatics tools integrated in the database with user-friendly interface will serve as a central information repository that could facilitate many studies related to oil plants for worldwide researchers.